THE ANALYSIS OF THE CORRELATION BETWEEN RECEPTIVE VOCABULARY AND GRADE TEN STUDENTS’ DESCRIPTIVE WRITTEN SKILL AT MA AL-HAMID - Agus Gunawan (Lingua, 2017)
This research consists of two variables, namely the independent variable (receptive vocabulary) and the dependent variable writing skill). The research consist of two variables, namely the receptive vocabulary and writing skill. The purpose of this research is to find out whether or not there is correlation between receptive vocabulary and writing skill. This research was conducted on the gradeten students at MA AL-HAMID, at in the academic year 2016/2017. Research method used in this research was correlational, quantitative and design was ex-post facto deisgn.To collect data the researacher used two instrument in the form of objective, multiple choice each numbering 30 for both X variable out of 50 question items for X and also 6 items for Y having been tried out in class X at MA AL-HAMID . the scores obtained from try-out class were used to analyze the validity, reliability, discrimination power and difficulty index of each question item in the two instruments.The population of this research was grade ten students consisting of 118 students occupying 3 classes. The number of sample was 40 students seating in class C taken from the population using cluster randomtechnique. The results obtained from samples were used to analyzethe data using statistical formulas of pearson’s product moment, preceded by normality and linierity test as the pre-requiste requirements for data analysis.The analysis using SPSS-based product moment formula produced significance (sig.) value of o.ooo. since the significance value was smaller than (<) alpha o.o5, Ho is rejected and Ha is accepted. Accordingly the research concludes that there is significant correlation correlation between receptive vocabulary and grade ten student’s writing skill at MA AL-HAMID in the academic year of 2016/2017.